Centralizacija v Sloveniji - Kušar, Simon (Geografski obzornik, 2025)
Centralization is the concentration of administrative-political and economic power and decision making, economic activities, jobs, and population in the capital city or central region. In Slovenia, it accelerated after 2000, mainly due to market forces, the construction of the motorway network, the sectoral management system of the state, and the unfinished reform of local self-government. It is reflected in the formation of new development patterns, with the Central Slovenia statistical region, home to the capital, standing out significantly. As a counterbalance to this developmental concentration, the state implements regional policy and promotes polycentric development.
Keywords: Central Slovenia statistical region; centralizacija; centralization; Osrednjeslovenska statistična regija; regional development; regionalizacija; regionalni razvoj; Slovenia; Slovenija